Effectiveness Of Using The Skeletal System Pocketbook on The Grade of Anatomy Practicum For Medical Students at Universitas Jambi - Enis, Rina Nofri; Hz, Tia Wida Ekaputri; Tarawifa, Susan; Aurora, Wahyu Indah Dewi; Shafira, Nyimas Natasha Ayu; Puspasari, Anggelia; Maharani, Citra; Halim, Rita; Virginsia, Sonya; Vivekanantharasa, Raveenthiran (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
ABSTRACT Background: Bone markings must be studied and mastered in learning skeletal system anatomy. The short and interesting material in the pocketbook helps students identify preparations during the practicum, increasing their understanding and gaining practical grades. Objective: This research aims to determine the effectiveness of using the Skeletal System pocketbook on grades practical anatomy block of the Integumentary System and Locomotion for medical students in the first semester of the Universitas Jambi in 2023. Method: This research used a quasi-experimental method with a pre-test and post-test control group. The 106 sample students were from the Medical Study Program at Universitas Jambi class of 2023. Result: The mean pre-test and post-test grades for students with pocketbooks were 61.86 and 78.04, while those without pocketbooks were 63.74 and 71.35. In the mean pre-test grade, there was no significant difference between the experimental and control groups' mean grades (p-value = 0.488). Meanwhile, in the mean post-test grades, there was a significant difference between the two groups (p-Value = 0.005), where the experimental group had a higher mean grade. Conclusion: There is a significant difference in using the skeletal system anatomy pocketbook on the grade of anatomy practicum for medical students at Universitas Jambi. Keywords: Anatomy, Practicum, Skeletal System, Pocket Book.